1997
DOI: 10.1124/mol.52.6.983
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone Activation of μ-Opioid Receptors Mutated at a Histidine Residue Lining the Opioid Binding Cavity

Abstract: The mu-opioid receptor is the principal site of action in the brain by which morphine, other opiate drugs of abuse, and endogenous opioid peptides effect analgesia and alter mood. A member of the seven-transmembrane domain (TM) G protein-coupled receptor (GPCR) superfamily, the mu-opioid receptor modulates ion channels and second messenger effectors in an opioid agonist-dependent fashion that is reversible by the classic opiate antagonist naloxone. Mutation of a histidine residue (His297) in TM 6 afforded agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 37 publications
10
63
0
Order By: Relevance
“…This result is similar to the peptide agonist PL017 for the -opioid receptor where a [H297Q] receptor replacement altered affinity 5-fold (Spivak et al, 1997). To provide possible insight into the molecular basis of this change, we made several GRPR (position 202) point mutants.…”
Section: Tablementioning
confidence: 89%
“…This result is similar to the peptide agonist PL017 for the -opioid receptor where a [H297Q] receptor replacement altered affinity 5-fold (Spivak et al, 1997). To provide possible insight into the molecular basis of this change, we made several GRPR (position 202) point mutants.…”
Section: Tablementioning
confidence: 89%
“…at the exoloop 2 or intraloop 2, which share 76 and 62% amino acid identity with the corresponding domains in the rGnRHR); in this setting, the particular structure of the rGnRHR antagonist might ultimately determine a preference for binding to the active receptor conformation of the hGnRHR and to both the inactive and active conformations of the rat counterpart, as would be expected for antagonist analogues. In fact, in a number of G protein-coupled receptors, including the GnRHR, mutations or species-dependent structural differences in either transmembrane domains (Strader et al 1989, Claude et al 1996, Noda et al 1996, Groblewski et al 1997, Han et al 1997, Spivak et al 1997, intraloops (Morin et al 1998, Wurch et al 1999 or exoloops (Sun et al 2001) may be limiting, to a variable extent, the level of maximal stimulation. It should be emphasized, however, that the effects of the compounds tested may be cell-specific and that depending on the relative levels of receptor, G proteins and other downstream effectors present in a particular tissue in vivo (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…14 On the other hand, conservative mutations (ie, those that do not disrupt hydrogen bonding interactions, eg, histamine or glutamine to asparagine), had only minor effects on ligand binding. 15 From these results, it was suggested that His VI:17 hydrogen-bonds to the opioids ' phenol.…”
Section: Introductionmentioning
confidence: 99%